2022
DOI: 10.1021/acsami.2c05886
|View full text |Cite
|
Sign up to set email alerts
|

Tetravalent Doping in Fluorite-Based Ferroelectric Oxides for Reduced Voltage Operations

Abstract: First-principles calculations show a reduced energy barrier for polarization switching via a bulk phase transition by doping of hafnium−zirconium oxide (HZO). The tetragonal P4 2 / nmc phase serves as a transition state for polarization switching of the polar orthorhombic Pca2 1 phase. Due to the high symmetry of the tetragonal phase, dopants can form more energetically favorable local oxygen bonding configurations in the tetragonal phase versus the orthorhombic phase. Significant bond strain is observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Second, a recent study has revealed a flat phonon dispersion in hafnia-ferroelectrics, which together with the presence of spacers, implies that collective ionic movement may not be so significant in these ferroelectrics. The ferroelectricity in hafnia-based oxides has been attributed to a polar Pca 2 1 orthorhombic phase of HfO 2 . , Recently, Chae et al studied the impact of tetravalent doping in fluorite-based ferroelectric oxides and proposed that the coordination number of 7 in the Pca 2 1 phase is related to the oxygen displacement and oxygen–metal bond breaking, which are responsible for the macroscopic polarizations . Besides the above special features, another puzzle is that other oxide ferroelectrics in the Pca 2 1 or similar structures are rarely reported, which renders it difficult to identify the material-specific properties of Pca 2 1 -HfO 2 from other members in the ionic ferroelectric family.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a recent study has revealed a flat phonon dispersion in hafnia-ferroelectrics, which together with the presence of spacers, implies that collective ionic movement may not be so significant in these ferroelectrics. The ferroelectricity in hafnia-based oxides has been attributed to a polar Pca 2 1 orthorhombic phase of HfO 2 . , Recently, Chae et al studied the impact of tetravalent doping in fluorite-based ferroelectric oxides and proposed that the coordination number of 7 in the Pca 2 1 phase is related to the oxygen displacement and oxygen–metal bond breaking, which are responsible for the macroscopic polarizations . Besides the above special features, another puzzle is that other oxide ferroelectrics in the Pca 2 1 or similar structures are rarely reported, which renders it difficult to identify the material-specific properties of Pca 2 1 -HfO 2 from other members in the ionic ferroelectric family.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of hafnium dioxide (HfO 2 )-based ferroelectrics in 2011, HfO 2 has emerged as a highly promising nonvolatile memory material. , This is primarily attributed to its robust ferroelectric properties at the nanoscale and compatibility with CMOS technology. However, the switchability of electric dipoles in HfO 2 significantly differs from that in traditional ferroelectrics, as hinted by its notably large coercive field ( E c ) and slow domain propagation. , The large E c in HfO 2 -based ferroelectrics (ranging from 1.0 to 2.2 MV/cm) brings significant challenges to device reliability and endurance. , Specifically, the elevated operational voltage required to write polarization above E c escalates the risk of charge injection and defect formation within devices. , Therefore, achieving a lower E c in HfO 2 -based ferroelectric thin films with fast domain motion is highly desirable to enhance reliability and achieve low-power operations.…”
mentioning
confidence: 99%